OPTIMIZATION OF OPERATING FRACTURING PARAMETERS FOR IMPROVING OIL PRODUCTION IN LOWER OLIGOCENE E RESERVOIR USING RESPONSE SURFACE METHOD, OFFSHORE VIETNAM: A CASE STUDY - Huu, Truong Nguyen (Vietnam Journal of Marine Science and Technology, 2019)
In the recent days, hydraulic fracturing technique has been widely used to improve oil production with different reservoir characteristics such as low or high formation permeability, low or high formation porosity, formation damage. However, previous research did not mention the optimization for fracturing parameters including the injection rate, injection time, and leak-off coefficient to stimulate the Oligocene E reservoir, which is based on optimum oil production performance at which maximum net present value has been achieved. The problems in the Oligocene reservoir are too low production rate due to high reservoir depth, high closure pressure up to 7,700 psi, low reservoir permeability, low porosity and geological structure with heterogeneous reservoir, high temperature, resulting in low conductivity. To deal with these problems, fracturing technique is the best choice to stimulate this reservoir. The study focuses on optimizing fracturing parameters by applying the CCD and RSM  by which economic production performance has been maximized at 119 $ in 10 years. The optimum fracturing parameters have been found as injection rate of 47 bpm, injection time of 119 minutes and leak-off coefficient of 0.003 ft/min0.5 in 50 pounds per thousand gallons of polymer (HPG). The optimal fracture geometry has been obtained with the fracture half-length of 1,449.44 ft and fracture width of 0.567 in. The rest of experimental laboratory is to measure fracture conductivity at 3,400 mD.ft in terms of proppant fracture concentration of 1.78 lb/ft2 and high closure pressure of 7700 psi. The post fractured well shows an increase in oil productivity of 7.5 folds